2023
DOI: 10.3390/foods12050963
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Characterization, and Bioactivity of Phenolic Compounds—A Case on Hibiscus Genera

Abstract: Phenolic compounds have recently gained interest, as they have been related to improvements in health and disease prevention, such as inflammatory intestinal pathologies and obesity. However, their bioactivity may be limited by their instability or low concentration in food matrices and along the gastrointestinal tract once consumed. This has led to the study of technological processing with the aim of optimizing phenolic compounds’ biological properties. In this sense, different extraction systems have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…High temperatures can decompose or modify thermosensitive bioactive compounds such as polyphenols and other antioxidants [ 36 ]. Also, very high temperatures can accelerate the co-extraction of other non-active components such as sugars and fiber; the antioxidant concentration in the extract would then decrease [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…High temperatures can decompose or modify thermosensitive bioactive compounds such as polyphenols and other antioxidants [ 36 ]. Also, very high temperatures can accelerate the co-extraction of other non-active components such as sugars and fiber; the antioxidant concentration in the extract would then decrease [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Yang and team, phenolic content and antioxidant activity are important aspect as a source of functional food 36 . It was recently reported that phenolic compounds have the potential to be used to develop functional foods for obesity 37 . Better food processing techniques are essential to retain bioactive phenolic compounds 38 .…”
Section: Specific Parametermentioning
confidence: 99%
“…The interest of the people in upgrading health through more environmentally friendly methods has increased rapidly over the past decades, which has led to a lot of research into traditional therapies as resources of elements with biofunctional characteristics [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this is because various vegetable have long been widely used not only for nutritional purposes but also for medical purposes [1,2]. Therefore, these components extracted from various vegetable are recognized as a resource of important biofunctional components [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation